Biofilm structure, dynamics, and ecology of an upscaled biocathode wastewater microbial fuel cell. Issue 3 (21st December 2020) - Leininger, Aaron; Yates, Matthew D.; Ramirez, Mark; Kjellerup, Birthe
Abstract: A microbial fuel cell (MFC) system containing modular half‐submerged biocathode was operated for 6 months in an 800 L flow‐through system with domestic wastewater. For the first time, spatial and temporal differences in biofilm communities were examined on large three‐dimensional electrodes in a wastewater MFC. Biocathode microbial community analysis showed a specialized biofilm community with electrogenic and electrotrophic taxa forming during operation, suggesting potentially opposing electrode reactions. The anodic community structure shifted during operation, but no spatial differences were observed along the length of the electrode. Power output from the system was most strongly influenced by pH. Higher power densities were associated with the use of solids‐dewatering filtrate with increased organic matter, conductivity, and pH. The results show that the biocathode was the rate‐limiting step and that future MFC design should consider the effect of size, shape, and orientation of biocathodes on their community assembly and electrotrophic ability. Abstract : Highlights: Large (800 L) biocathode microbial fuel cell was operated for 6 months with real domestic wastewater. Uniquely specialized 3D biocathode was highly enriched with Desulfuromonas spp. Spatial and temporal trends in microbial community structure were discerned. High‐strength solids‐dewatering wastewater was associated with improved power despite high ammonia.